Insights on HPV vaccination in the United States from mothers' comments on Facebook posts in a randomized trial - David B. Buller; Barbara J. Walkosz; Julia Berteletti; Sherry L. Pagoto; Jessica Bibeau; Katie Baker; Joel Hillhouse; Kimberly L. Henry (Taylor & Francis Group, 2019)
In the United States, parents' health beliefs affect HPV vaccination decisions for children. Our team acquired insights into mothers' health beliefs from their reactions and comments to posts on HPV vaccination in a social media adolescent health campaign in a randomized trial (n = 881 mothers; 63.1% reported daughters had 1+ doses of the HPV vaccine) evaluating communication intended to reduce daughters' indoor tanning. A total of 10 HPV vaccination messages in didactic (n = 7) and narrative (n = 3) formats were posted on vaccination need, uptake, and effectiveness and stories of young women who died from cervical cancer and a mother's decision to vaccinate her daughters. These posts received 28 reactions (like, love, and sad buttons; mean = 2.8 per post) and 80 comments (mean = 8.0 per post). More comments were favorable (n = 43) than unfavorable (n = 34). Data was not collected on views for posts. The most common favorable comment reported that daughters were vaccinated (n = 31). Unfavorable comments cited safety concerns, lack of physician support, distrust of pro-vaccine sources, and increased sexual activity of daughters. Mothers posting unfavorable (18.2%) as opposed to favorable (78.6%) comments or not commenting (64.0%) were less likely to have had their daughters vaccinated (chi-square = 22.27, p < 0.001). Favorable comments often did not state reasons for vaccinating. Concerns about lack of vaccine safety remain a barrier. Mothers may express distrust in pro-vaccine sources to reduce discomfort with not vaccinating daughters to reduce their risk for HPV infection. Many mothers who remained silent had vaccinated daughters, which suggests they did not resisit HPV vaccination.